Forecasting Red Onion Prices in Riau Islands Using the Seasonal Autoregressive Integrated Moving Average (SARIMA) Method: Peramalan Harga Bawang Merah di Kepulauan Riau Menggunakan Metode Seasonal Autoregressive Integrated Moving Average (SARIMA) - Revika Inta Nur Kholifah; Ihsan F athoni Amri; M Al Haris; Nasyiatul Izzah; Miftakhiyah Fazza Baita; Siti Nurhalisa (Department of Sains Data UNIMUS Universitas Muhammadiyah Semarang, 2024)
The price of shallots is one of the crucial commodities that affects economic stability and community welfare in the Riau Islands. The main factors influencing shallot production are seed variety, land, and weather. This study aims to forecast the price of shallots in the Riau Islands using the Seasonal Autoregressive Integrated Moving Average (SARIMA) method. The data used in this study is sourced from official data and covers a specific period to ensure the accuracy of the forecasting model. The SARIMA (0 1 1) (0 1 1)5 model with the smallest AIC of 2211.59 was selected as the best model based on data analysis and model performance evaluation, with a Mean Absolute Percentage Error (MAPE) of 2.690835 percent, indicating that the model's ability to predict shallot prices in the Riau Islands is very accurate. The prediction results indicate that the price of shallots will decrease in the coming days according to the developed model. Based on these results, this forecast is expected to serve as a reference for the government and market participants in decision-making related to the production, distribution, and control of shallot prices in the Riau Islands.